PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN E-LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INSTALASI PENERANGAN LISTRIK - Hafiz Bakri; Muhammad Amin (Universitas Negeri Medan, 2022)
Abstract This study aims to determine the differences in student learning outcomes between the experimental class using the Problem Based Learning learning model assisted by E-Learning and the control class using the ordinary Problem Based Learning learning model. This study uses a quasi-experimental method with a Posttest Only, Non-Equivalent Control Group Design model. The number of research subjects was 59 students, consisting of 30 students from class XI TITL 1 as the experimental class and 29 students from class XI TITL 2 as the control class. The data collection technique used is a written test in the form of multiple choice which has been tested for validity, reliability, level of difficulty, and discriminatory power. The results of the study obtained that the average value of student learning outcomes in the experimental class was 84.96. While the control class is 77.68. From the results of the calculation of the hypothesis test, it is obtained that t_count is 2.14 and t_table is 2.002, then t_count > t_table or 2.14 > 2.002, so it can be concluded that the alternative hypothesis (Ha) in this study is accepted as well as rejecting the null hypothesis (Ho) in other words the results The learning outcomes of class XI TITL students using the Problema Based Learning learning model assisted by E-Learning are higher than student learning outcomes using the Ordinary Problem Based Learning learning model. Keywords: Quasi Experiment, PBL E-Learning, PBL, Learning Outcomes. AbstrakPenelitian ini bertujuan untuk mengetahui perbedaan hasil belajar siswa antara kelas eksperimen yang menggunakan model pembelajaran Problem Based Learning berbantuan E-Learning dengan kelas kontrol yang menggunakan model pembelajaran Problem Based Learning biasa. Penelitian ini menggunakan metode quasi eksperimen dengan model Posttest Only, Non-Equivalent Control Group Design. Jumlah subjek penelitian 59 orang peserta didik, yang terdiri 30 peserta didik kelas XI TITL 1 sebagai kelas eksperimen dan 29 peserta didik kelas XI TITL 2 sebagai kelas kontrol. Teknik pengumpulan data yang digunakan adalah tes tertulis berbentuk pilihan ganda yang telah terlebih dahulu diuji validitas, reliabilitas, tingkat kesukaran, dan daya pembeda. Hasil penelitian diperoleh nilai rata-rata hasil belajar siswa pada kelas eksperimen yaitu 84,96. Sedangkan kelas kontrol 77,68. Dari hasil perhitungan uji hipótesis diperoleh 2,14 dan adalah 2,002, maka > atau 2,14 > 2,002, sehingga dapat disimpulkan bahwa hipótesis alternatif (Ha) dalam penelitian ini diterima sekaligus menolak hipótesis nihil (Ho) dengan kata lain hasil belajar siswa kelas XI TITL dengan menggunakan model pembelajaran Problema Based Learning berbantuan E-Learning lebih tinggi dari hasil belajar siswa dengan menggunakan model pembelajaran Problema Based Learning Biasa. Kata Kunci : Quasi Eksperiment, PBL E-Learning, PBL, Hasil Belajar.